Réponses

2014-03-27T22:12:38+01:00
Réduire les expressions:

OUI
A= 3x + 5 + 12x + 7
A= 3x + 12x + 5 + 7
A= 15x + 12

NON
B= 4 - 6y - 3 + 4y
B= 4 - 3 - 6y + 4y
B= 1 - 2y

OUI
C= -2x - 7 + 5x - 7
C= -2x + 5x - 7 - 7
C= 3x - 14

OUI
D= 2x - 7 + 5x + 7
D= 2x + 5x - 7 + 7
D= 7x + 0
D= 7x

OUI
E= 15 - y - 5 + 3y
E= -y + 3y + 15 - 5
E= 2y + 10

OUI
F= -6x + 7 - 6x - 2
F= -6x - 6x + 7 - 2
F= -12x + 5

Tout juste sauf la B! :)
pourrais tu m'aider pour l'exo de la randonnée que j'ai posté avant.STP MERCI